2013
DOI: 10.1007/978-1-62703-640-5_13
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized Neuronal Cultures

Abstract: The culturing of neurons results in formation of the layer of neurons with random extensive overlapping outgrowth. To understand specific roles of somas, axons and dendrites in complex function of neurons and to identify molecular mechanisms of biological processes in these cellular compartments various methods were developed. We utilized AXon Investigation System (AXIS™) manufactured by Millipore. This device provides an opportunity to orient neuronal outgrowth and spatially isolate neuronal processes from ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Our data suggest that either through transfection, or transduction, Tat causes mtDNA damage in neuronal cells. Previously, we confirmed that ultrapure Tat protein or short PTD-Tat (47-57 amino acids) was entering into neuronal cells or nucleus as early as after 40 minutes post-treatment [ 37 , 38 ]. Our and other research groups investigated features and characteristics of Tat protein to achieve an efficient transduction and to avoid degradation or cleavage prior its transportation into nucleus [ 39 43 ].…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Our data suggest that either through transfection, or transduction, Tat causes mtDNA damage in neuronal cells. Previously, we confirmed that ultrapure Tat protein or short PTD-Tat (47-57 amino acids) was entering into neuronal cells or nucleus as early as after 40 minutes post-treatment [ 37 , 38 ]. Our and other research groups investigated features and characteristics of Tat protein to achieve an efficient transduction and to avoid degradation or cleavage prior its transportation into nucleus [ 39 43 ].…”
Section: Resultsmentioning
confidence: 77%
“…PCR conditions were as follows; activation 95°C 5 min, PCR 45 cycles: 95°C 10 sec, 60°C 20 sec, 72°C 30 sec, melting curve (95-65°C), cool to 40°C 30 sec. [ 37 ]. For relative quantification, the expression level of genes was normalized to the housekeeping gene β-actin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal brain tissue (gestational age 16–18 weeks) was obtained from elective abortion procedures performed in full compliance with National Institutes of Health and Temple University ethical guidelines. Human Primary Fetal Neuronal Culture was prepared as described previously (Darbinyan et al, ,). The experiments were performed in triplicate with different fetal tissue from different donors for each experiment in single passage.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed protocol of using this type of device has been reported in a previous chapter [13]. Alternatively, a fabrication protocol can be followed if custom-designed patterns are preferred [14].…”
Section: Methodsmentioning
confidence: 99%